3D printing of poly(ε-caprolactone)/poly(D, L-lactide-co-glycolide)/hydroxyapatite composite constructs for bone tissue engineering. Issue 14 (27th June 2018) - Moncal, Kazim K.; Heo, Dong N.; Godzik, Kevin P.; Sosnoski, Donna M.; Mrowczynski, Oliver D.; Rizk, Elias; Ozbolat, Veli; Tucker, Scott M.; Gerhard, Ethan M.; Dey, Madhuri; Lewis, Gregory S.; Yang, Jian; et al.
Abstract: Abstract : Three-dimensional (3D) printing technology is a promising method for bone tissue engineering applications. For enhanced bone regeneration, it is important to have printable ink materials with appealing properties such as construct interconnectivity, mechanical strength, controlled degradation rates, and the presence of bioactive materials. In this respect, we develop a composite ink composed of polycaprolactone (PCL), poly(D, L-lactide- co -glycolide) (PLGA), and hydroxyapatite particles (HAps) and 3D print it into porous constructs. In vitro study revealed that composite constructs had higher mechanical properties, surface roughness, quicker degradation profile, and cellular behaviors compared to PCL counterparts. Furthermore, in vivo results showed that 3D-printed composite constructs had a positive influence on bone regeneration due to the presence of newly formed mineralized bone tissue and blood vessel formation. Therefore, 3D printable ink made of PCL/PLGA/HAp can be a highly useful material for 3D printing of bone tissue constructs.